Gender Role and Patriarchal Ideology in Maleficent: Mistress of Evil (2019) - Khika Adistiadiva (Cultural Narratives, 2026)
While contemporary cinema increasingly features dominant female figures to seemingly challenge patriarchal norms, these representations often harbor underlying traditional biases. This study investigates this ideological complexity in Maleficent: Mistress of Evil (2019) by analyzing the portrayals of Maleficent and Queen Ingrith. This research uses the theory of character and characterization by Boggs & Petrie and feminist film theory by Haskell. This research finds the characteristics of Maleficent and Queen Ingrith, such as being powerful, rational, heroic, leadership and independent. Both of them are protector and queen in their respective kingdoms. Although the two female main characters are described as equally dominant, they are described as having significant differences. Maleficent as a woman, although she is described as a dominant woman, but she supports a traditional gender role. Meanwhile, Queen Ingrith is also portrayed as a dominant woman in the film, but she opposes traditional gender roles. This makes the film challenge the ideas of patriarchal ideology. Due to the different gender roles that both of them have, they get different treatment from other characters in the film; Maleficent gets good treatment, while Queen Ingrith gets bad treatment. This study concludes that rather than fully dismantling patriarchal ideology, the film subtly reinforces it by rewarding dominant women who align with traditional maternal roles, while punishing those who reject them. Consequently, this implies that mainstream media's portrayal of female empowerment often remains confined within patriarchal boundaries, highlighting the need for a more critical consumption of modern pseudo-progressive narratives.